2014
DOI: 10.3389/fpsyg.2014.00020
|View full text |Cite
|
Sign up to set email alerts
|

The influences of age on olfaction: a review

Abstract: Decreased olfactory function is very common in the older population, being present in over half of those between the ages of 65 and 80 years and in over three quarters of those over the age of 80 years. Such dysfunction significantly influences physical well-being and quality of life, nutrition, the enjoyment of food, as well as everyday safety. Indeed a disproportionate number of the elderly die in accident gas poisonings each year. As described in this review, multiple factors contribute to such age-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
462
1
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 510 publications
(498 citation statements)
references
References 262 publications
(306 reference statements)
21
462
1
14
Order By: Relevance
“…The loss of smell has been reported in a number of studies and is associated with aging [1,2], gender [3] and various health ailments including neurodegenerative diseases such as Alzheimer's disease (AD) [2,[4][5][6]. It has been reported that olfactory dysfunction is one of the earliest sign of neurodegeneration in AD [7].…”
Section: Introductionmentioning
confidence: 99%
“…The loss of smell has been reported in a number of studies and is associated with aging [1,2], gender [3] and various health ailments including neurodegenerative diseases such as Alzheimer's disease (AD) [2,[4][5][6]. It has been reported that olfactory dysfunction is one of the earliest sign of neurodegeneration in AD [7].…”
Section: Introductionmentioning
confidence: 99%
“…Szacunki dotyczące częstości występowania zaburzeń funkcji olfaktorycznej wskazują na jej powszechność. Według różnych badaczy odsetek obiektywnie potwierdzonych zaburzeń węchu wzrasta z 11-24% w wieku średnim do 37-80% w wieku starczym [1,8,11,[15][16][17][18]. Około połowa populacji USA w wieku 65-80 lat cierpi na różnego stopnia utratę sprawności węchu.…”
Section: Związana Z Wiekiem Utrata Sprawności Węchowejunclassified
“…Estimates concerning the occurrence of olfactory dysfunction suggest its common prevalence. According to various researchers, a percentage of the objectively confirmed smell dysfunctions increases from 11-24% in the middle age to 37-80% in old age [1,8,11,[15][16][17][18]. Approximately half of the US population between the age of 65-80 suffers from various degrees of olfactory loss.…”
Section: Age-related Olfactory Ability Lossmentioning
confidence: 99%
“…The thickness, extent and integrity of the olfactory mucosa decreases significantly with age, and neuroepithelial degeneration seems to be an inevitable feature of human aging with significant reduction in olfaction 29,30,31 .…”
mentioning
confidence: 99%